2016
DOI: 10.3201/eid2201.150544
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Epidemic Diarrhea Virus and Discovery of a Recombinant Swine Enteric Coronavirus, Italy

Abstract: Porcine epidemic diarrhea virus (PEDV) has been detected sporadically in Italy since the 1990s. We report the phylogenetic relationship of swine enteric coronaviruses collected in Italy during 2007–2014 and identify a drastic shift in PEDV strain variability and a new swine enteric coronavirus generated by recombination of transmissible gastroenteritis virus and PEDV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
195
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(208 citation statements)
references
References 14 publications
11
195
1
1
Order By: Relevance
“…In this study, we describe PEDVs circulating in the USA as the US PEDV prototype strain and US PEDV S-INDEL-variant strain. Since the PED outbreak in the USA, detection of US prototype-like PEDV has been reported in Canada, Mexico, Taiwan, South Korea, Japan and Ukraine (Dastjerdi et al, 2015;Lin et al, 2014;Ojkic et al, 2015;Van Diep et al, 2015;Vlasova et al, 2014); detection of US S-INDEL-variantlike PEDV has been reported in South Korea, Germany, Belgium, France, Portugal, Japan, Italy and Austria (Boniotti et al, 2016;Grasland et al, 2015;Hanke et al, 2015;Mesquita et al, 2015;Stadler et al, 2015;Steinrigl et al, 2015;Theuns et al, 2015;Yamamoto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we describe PEDVs circulating in the USA as the US PEDV prototype strain and US PEDV S-INDEL-variant strain. Since the PED outbreak in the USA, detection of US prototype-like PEDV has been reported in Canada, Mexico, Taiwan, South Korea, Japan and Ukraine (Dastjerdi et al, 2015;Lin et al, 2014;Ojkic et al, 2015;Van Diep et al, 2015;Vlasova et al, 2014); detection of US S-INDEL-variantlike PEDV has been reported in South Korea, Germany, Belgium, France, Portugal, Japan, Italy and Austria (Boniotti et al, 2016;Grasland et al, 2015;Hanke et al, 2015;Mesquita et al, 2015;Stadler et al, 2015;Steinrigl et al, 2015;Theuns et al, 2015;Yamamoto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For amplifi cation, the commercial OneStep RT-PCR kit (Qiagen, Germany) was used with primers that amplifi ed the 651 bp fragment of spike protein (S) gene of PEDV (P1 (TTCTGAGTCACGAACAGCCA, 1466-1485) and P2 (CATATGCAGCCTGCTCTGAA, 2097-2116)), 859 bp fragment of S gene of TGEV (T1 (GTGGTTTTGGTYRTAAATGC, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and T2 (CACTAACCAACGTGGARCTA, 855-874)), and 309 bp fragment of gene segment 6 of porcine group A rotavirus (rot3 (AAAGATGCTAGGGACAAAATTG, 57-78) and rot5 (TTCAGATTGTGGAGCTATTCCA, 344-365)) as described by Song et al [23]. Briefl y, the reaction was performed in a total volume of 25 μl as follows: 8 μl of nuclease free water, 5 μl of 5 x PCR buffer, 1 μl of dNTP mix (containing 10 mM of each dNTP), 1 μl of 20 μM solution of each primer, 1 μl of one step RT-PCR enzyme mix and 4 μl of RNA template.…”
Section: Molecular Detection and Characterizationmentioning
confidence: 99%
“…The only well documented is a typical PED epidemic in Europe which occurred during the winter of 2005-2006 in Northern Italy [16]. Recently, the PED-confi rmed outbreaks have been reported in several Central European countries: Portugal [7], Germany [15], Austria [17], France [18], Belgium [19], Ukraine [20], Italy [21] and Slovenia [22]. The full genome sequencing of recent PEDV strains from Germany, Belgium and France [17][18][19] shows that they are all highly similar and closely related to S-INDEL strains from USA [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…57,85 Possible recombination events might contribute to a rapid evolution of US strains. 57 Recently, OH851-like strains have been detected in South Korea 56 and Japan 81 in Asia, and Germany, 15,16 Italy, 17 the Netherlands, 18 Belgium, 19 France, 20 Portugal, 22 Slovenia, 21 and Austria 21 in Europe. A novel variant TC-PC22A (GenBank accession number KM392224), which has a large deletion (197-aa) in the N-terminal portion of the S protein, was recently isolated in the United States.…”
Section: Asiamentioning
confidence: 99%
“…15 Thereafter, 20 Italy, 17 Austria, 21 Belgium, 19 the Netherlands, 18 Portugal, 22 and Slovenia. 21 Different from the aforementioned European countries, in 2014, severe PED outbreaks occurred in Ukraine, and the isolates clustered phylogenetically with genotype IIa US strains.…”
Section: Europementioning
confidence: 99%